(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2019)
The research aims to prepare a report by the external auditor (Federal Office of Financial Supervision) for the control environment it is includes financial control, commitment and performance of the North Oil Company (extractive) according to the causes of pollution. The research problem it is not the Federal Office of Financial Supervision preparation a report on the things the environment include the prevent or reduction failure the administration of the causes of the pollution caused by oil mining industry by both bad planning or operational or related to efficient human resources as well as of technology to use and resulting from non-compliance local laws and instructions, as well as the inefficiency of spending on environmental issues by The research Hypothec is that environmental control for all kinds (financial Audying ,control of commitment and control performance)By the external auditor contributes to reducing or minimizing the negative environmental effects through verifying compliance with local laws and regulations as well as the efficiency of spending on environmental matters by extractive companies It is the most important conclusions the company had not preparation programs (Plan) for the repair of environmental assets so as an increase quantity of leaky oil from pipeline ,So does not have an official landfills and industrial waste, unlike of the laws as well as the lack of precision in determining the need (planned) of the necessary supplies of cars , machinery and industrial security requirements as well as lack of the staff in the environmental issues professionals .